Penerapan Akuntansi Zakat dan Infak/Sedekah pada Badan Amil Zakat Nazional (BAZNAS) Kota Gorontalo - Bakri Bakri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
The National Zakat Agency (BAZNAS) of Gorontalo city was formed, to collect zakat and infaq / alms funds and distribute them according to the guidance of Al-Qur'an and Al-Hadith. This study aims to determine whether the application of zakat and infaq accounting by Gorontalo city BAZNAS has been applied based on the Statement of Financial Accounting Standards 109 of 2008. From the results of research conducted by direct observation, interviews, and documentation, it is found that not yet fully applying accounting for zakat, infaq and in accordance with the Statement of Financial Accounting Standards 109 of 2008, namely journal recording for non-halal funds that are recognized as an addition to infa funds. In addition, the report on changes in funds does not present reports on changes in non-halal funds and reports on changes in assets under management. This is due to several obstacles faced by amil, namely regarding the Management Information System of the National Amil Zakat Agency (SIMBA) and also does not really understand the accounting for zakat and alms in accordance with the Statement of Financial Accounting Standards 109